Enhanching Farmer Group Management through Organizational Formation and Matrix Preparation in Rahabite Village, Toari District - Handayani, Fitrianti; Ali Bain; Sarinah; Nur Santy Asminaya; La Ode Muhsafaat; La Mpia; Musadia Afa; Sitti Aisyah May Wulandari; Asni; Sugirah Hidayah Rauf; Muhammad Gazali; Rahmat Tata Pratama; Muhammad Al Fandi; Asriatno, Okto (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2025)
Farmers in Rahabite, Toari District, have historically operated individually, thereby encountering typical agricultural constraints, particularly diminished bargaining power in product marketing and limited access to information. The primary objective of this Community Service (PkM) activity was to facilitate the establishment of a functional and independent Farmers' Business Group (Kelompok Usaha Tani or KUT). The implementation method employed a structured participatory approach, aligned with a pre-designed activity matrix. The PkM stages comprised: (1) Preparation, involving observation, interviews, and coordination with village officials; (2) Implementation, encompassing socialization regarding the importance of collective action, facilitation of deliberations for KUT formation, board election, and the drafting of Articles of Association/Bylaws (AD/ART); and (3) Post-Implementation, consisting of initial mentoring and evaluation. The results demonstrated a 100% success rate based on established indicators: the establishment of KUT